Analysis of patient outcomes following proton radiation therapy for retinoblastoma - Mouw, Kent W. (Adv Radiat Oncol, 2016)
PURPOSE: Proton radiation therapy (PRT) is used to treat patients with retinoblastoma (RB) and has the potential to minimize exposure of normal tissue to radiation and thus decrease the risk of toxicity and second malignancies. However, comprehensive analyses of long-term patient outcomes are not available. METHODS AND MATERIALS: Patients with RB who were treated with PRT at our institution between 1986 and 2012 were invited to participate in a study that was designed to assess long-term outcomes. Patients who were enrolled in the study underwent a comprehensive analysis that included oncologic, ophthalmic, endocrine, cephalometric, and quality of life (QOL) assessments. RESULTS: A total of 12 patients were enrolled in this study. The average length of follow-up was 12.9 years (range, 4.8-22.2 years). All study patients had bilateral disease, and the disease and visual outcomes were similar to the outcomes for all patients with RB who were treated with PRT over the same time period at our institution. An analysis of endocrine-related test results revealed no growth abnormalities or hormonal deficiencies across the cohort. Magnetic resonance imaging scans and external cephalometry showed that PRT was associated with less facial hypoplasia than enucleation. Patient and parent-proxy QOL assessments revealed that treatment for RB did not appear to severely affect long-term QOL. CONCLUSIONS: In addition to providing an opportunity for long-term disease control and functional eye preservation, PRT does not appear to be associated with unexpected late visual, endocrine, or QOL effects in this cohort of patients with RB.